Local Administration of β-Blockers for Infantile Hemangiomas: A Systematic Review and Meta-analysis. Issue 2 (February 2015) - Ovadia, Steven A.; Landy, David C.; Cohen, Erin R.; Yang, Ethan Y.; Thaller, Seth R.
Abstract : Background: Infantile hemangiomas (IHs) are a common pediatric lesion. Orally administered β-blockers have been reported as effective in treating these lesions. However, oral administration is also associated with systemic adverse effects. Treatment with locally administered β-blockers may provide acceptable efficacy with lower incidence of adverse effects. This may offer a better first-line treatment. Methods: PubMed was searched through March 2014 for studies reporting patient-level response of 5 or more patients treated with intralesional propranolol, topical timolol, or topical propranolol for cutaneous IHs. Rates of response to treatment, defined as clinically significant regression, were combined using random-effects meta-analysis. Results: Ninety-four articles were identified. Seventeen articles met the study criteria. These studies primarily focused on superficial IHs. Response rates for topical propranolol and topical timolol were not significantly different, 76% [95% confidence interval (CI), 62%–86%] and 83% (95% CI, 65%–93%), respectively ( P = 0.45). Prospectively conducted studies reported lower response rates compared to retrospective studies for both topical propranolol ( P = 0.06) and topical timolol ( P < 0.01). When only prospectively conducted studies were included, response rates for topical propranolol and topical timolol were not significantly different, 72% (95% CI, 57%–83%) and 72% (95% CI, 53%–86%), respectively ( P = 0.98). Significant adverse effects were rare. Only 1 case of sleep disturbance was reported across 554 patients from all studies. Conclusions: Topically administered β-blockers are an effective treatment for superficial IHs that pose few adverse effects and should be considered for primary treatment.